2018
DOI: 10.12809/hkmj154764
|View full text |Cite
|
Sign up to set email alerts
|

Implications of nipple discharge in Hong Kong Chinese women

Abstract: Introduction:There are no recent data on nipple discharge and its association with malignancy in Hong Kong Chinese women. This study reported our 5-year experience in the management of patients with nipple discharge, and our experience of mammography, ultrasonography, ductography, and nipple discharge cytology in an attempt to determine their role in the management of nipple discharge. Methods:Women who attended our Breast Clinic in a university-affiliated hospital in Hong Kong were identified by retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the current study; in addition to age and abnormal imaging; the bloody unilateral uniductal induced discharge with suspicious pathology are red flags of malignancy. In our study; 75% of cancer patients had bloody discharge which is similar to the several studies and meta-analyses which concluded that bloody nipple discharge is found to be associated with underlying malignancy [20][21][22] while in one study conducted with Røpcke., et al [18] who did not find a significant association between bloody discharge and invasive cancer. This difference may be due to the low number of cases included in each study as well as the difference in selection criteria [18].…”
Section: Resultssupporting
confidence: 89%
“…In the current study; in addition to age and abnormal imaging; the bloody unilateral uniductal induced discharge with suspicious pathology are red flags of malignancy. In our study; 75% of cancer patients had bloody discharge which is similar to the several studies and meta-analyses which concluded that bloody nipple discharge is found to be associated with underlying malignancy [20][21][22] while in one study conducted with Røpcke., et al [18] who did not find a significant association between bloody discharge and invasive cancer. This difference may be due to the low number of cases included in each study as well as the difference in selection criteria [18].…”
Section: Resultssupporting
confidence: 89%
“…Overall, these specificity and sensitivity data are echoed across individual studies of patients presenting with symptomatic nipple discharge. 16 , 17 Interestingly, the diagnostic accuracy of nipple cytologic analysis of patients with PND is similar to that of other diagnostic tests, with sensitivities ranging from a high of 70 % for both ultrasound and MRI to a specificity high of 79 % for mammography. Critically, in the case of a patient whose sole symptom is nipple discharge, no individual diagnostic test, whether imaging or cytologic, yielded a sensitivity or specificity high enough for its use as a stand-alone test.…”
Section: Discussionmentioning
confidence: 68%
“…59 The primary finding of this meta-analysis is that the sensitivity of NAF cytology for cancer detection in asymptomatic women is poor [0.64 (95% CI 0.62-0.66)] and yet the specificity is extremely high [0.97 (95% CI 0.97-0.98)]. Overall, high specificity and low sensitivity data is echoed across individual studies and also in those presenting with symptomatic nipple discharge, 60,61 with a diagnostic accuracy for malignancy of only 31%. 60 The reason for such low sensitivity of nipple aspirate fluid is that discharge is often ''physiological'' in nature, has a generally high acellular or paucicellular composition, 58,62,63 and therefore is thought to consist almost exclusively of background debris and/or proteinaceous material.…”
Section: Discussionmentioning
confidence: 90%